Hypnotherapy for the achievement of appropriate indicators of the childbirth in pregnant adolescents with psychological symptoms derived from the COVID - 19 - Adolfo Rafael Lambert Delgado; Alberto Erconvaldo Cobián Mena; Frank David Alcalá Ciria; Yosmel Toirac Fernández; Michel Torres Leyva; Yanet Silva Albear (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The adolescence covers between the 10 and 19 years, period in which the pregnancy has higher risk of complications in the mother and the newborn. The COVID-19 increases the possibility of emergence of psychological complications that impact negatively in pregnancy and childbirth if they are not assisted. In this study the patients were treated by means of hypnotherapy.    Objective: To evaluate the effectiveness of the hipnotherapeutic pattern for the achievement of appropriate indicators of childbirth in pregnant adolescents with psychological symptoms derived from the COVID-19.  Methods: A study of hipnoterapeutic intervention was carried out in 9 pregnant adolescents with psychological symptoms derived from the COVID - 19, admitted to the Eastern Maternal Nutritional Hospital in Santiago de Cuba, from April to June, 2020. The patients had follow up until after the childbirth.   Results: It was found that 7 pregnant women (77.8 %) had eutocic childbirth and perceived the pain as medium; in 66.7 % there was not necessity to use analgesic and 8 of them (88.9 %)  didn't present complications.  Also, all the newborns had a normal apgar.   Conclusions: The hipnotherapeutic pattern for the treatment of pregnant adolescents with psychological symptoms derived from the COVID-19 was able to improve indicators of  childbirth and other parameters associated with it.